Safe and sound: why a robust and workable data security policy is fundamental in healthcare programs - Jessop, Dale (mHealth, 2016)
There is no doubt that health and wellness data is becoming increasingly connected. Digital technology is now advancing at lightning pace and becoming more affordable, the cost of healthcare is rising and becoming a drain on national economies across the world. It is then obvious that healthcare organisations should adopt digital technology—however, with this new shift comes a whole host of security issues.